HUMAN-OPERATOR IN THE FUTURE SYSTEM OF AIR TRAFFIC SERVICES - Харченко, В; Рудас, С. (Proceedings of National Aviation University, 2012)
We consider the mutual influence of the operator of the Air Navigation System (Air Traffic Controller) and the technical component poliergatics system of air traffic services (ATS) on the reliability of the ATS, with the work of an operator in the team.